ENTREPRENEURIAL MARKETING IN IMPROVING MARKETING PERFORMANCE BENGKALIS REGENCY WOVEN FABRIC MSMES - Mashur Fadli; Heriyanto, Meyzi; Augustin, Jeneva (Riau International Conference on Economics, Business and Accounting, 2024)
This research aims to measure entrepreneurial marketing in improving the marketing performance of woven fabric MSMEs in the Bengkalis district. This research uses a quantitative descriptive approach. Primary data was collected through a survey of 78 respondents with a census sample and Partial Least Square (PLS) statistical techniques to process data and test hypotheses. The research results show that proactive innovation has a direct and significant effect on marketing performance, calculated risk-taking has no direct effect on marketing performance, innovativeness has no direct effect on marketing performance, value creation has no direct effect on marketing performance, opportunity focus has no direct effect on marketing performance, resource Leveraging has a direct and significant effect on marketing performance and customer intensity does not have a direct effect on the marketing performance of Bengkalis Regency Woven Fabric MSMEs